ECOSOPHY FOUNDATION WITH PLACE-BASED EDUCATION MODEL CLINICAL LEGAL EDUCATION - Mohammad Alvi Pratama; Eva Laila Rizkiyah (IBLAM Law Review)
Environmental destruction arises as a result of human wickedness and the absence of legislative acknowledgement of environmental integrity. Historically, the anthropocentric conception of law resulted in legislation serving as a tool for taming and othering nature, with nature existing only as a means to an end: human wellbeing (in terms of human rights). As a legal tool, it might be regarded as natural legitimacy degrading the environment, particularly through anthropocentric power relations, in the name of developing a risk management measuring tool that does not safeguard, but rather perpetuates, this ecological business. If the law remains dominated by an anthropocentric perspective, it will continue to be a mechanism for promoting and legitimizing environmental destruction; environmental law is still biased in favor of human wellbeing, not ecological integrity. As a result of this research, it is important to develop a additional learning model for CLE, one that is based on the Ecosophy (Ecological Philosophy) paradigm, which underpins the Deep Ecology perspective with Pedagogy Place Based Education (PBE). This is a qualitative descriptive-analytical method for expressing the legal situation & needs. The study’s findings indicate that the predominance of anthropocentric perspectives in law, particularly in determining the personality of legal subjects who are exclusively human and human interests (such as companies), must be reinterpreted. This perspective establishes the role of law as a way of taming and othering nature, and more precisely, as a means of instrumentalizing and legitimizing environmental destruction under the guise of exploiting nature. Humans are, philosophically speaking, a component of the ecology. Human equality with nature is consistent with Deep Ecology beliefs. Thus, the expansion of the personality of legal subjects to include non-humans ensures that they receive their rights and are classified as vulnerable groups. Deep Ecology can be used to demonstrate that this PBE model for CLE must have a non-anthropocentric perspective and be more open-minded through the Ecosophy education model: PBE, in order for students to critically and empathetically see the world from a deep-holistic perspective, that vulnerable groups are not limited to humans, but also include nature. This understanding will result in law students who become environmental activists, ensuring that the future of law recognizes environmental integrity and does not justify environmental destruction.